STRATEGI BELAJAR KELOLOSAN JAPANESE LANGUAGE PROFICIENCY TEST N1 (STUDI KASUS MAHASISWA SASTRA JEPANG) - Agus Budi Cahyono (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
Japanese Language Proficiency Test (JLPT) organized by The Japan Foundation twice a year in July and December is an international test which aims to measure the Japanese language skill of Japanese language learners around the world. JLPT has 5 levels in which level N5 is the lowest or basic level, while N1 is the highest or proficient level which is considered on par with the Japanese native speakers. Level IV students in school year 2016/2017 who have been able to achieve JLPT level N1 are proud achievements for Japanese Literature Study Program of Brawijaya University. Therefore, this research aims to see the learning strategy of Japanese language used by students who achieved JLPT level N1 in period II of 2016. In fact, they never visit Japan to stay, study, or even travel. The learning strategies of students studied through foreign language learning strategy as revealed by Oxford (1990) are memory, cognitive, and compensation in the category of direct strategy as well as metacognitive, affective, and social strategies in the category of indirect strategy. The used research methodology is qualitative research methodology of case study through questionnaire, interview, and observation. The research shows the result that learning strategy of Japanese language used by students to achieve JLPT level N1 are memory, cognitive, metacognitive, and compensation strategies by using several medias from anime (Japanese cartoon), Japanese movie, video game, Japanese songs, and even Japanese books like manga (Japanese comic) and novel. These students seldom use affective and social strategies. It is known from their lecturer that these students are less proficient in socialization and oral production.